Optimalisasi Akad Muzara’ah pada Bank Syariah - Irwan Rahmatullah Putra; M. Syahrul Hajj; Ikayanti Ikayanti (Maliyah : Jurnal Hukum Bisnis Islam, 2018)
This article discusses the optimization of muzara’ah contracts in Islamic banks. This article is the result of a literature review and qualitative research. Data comes from literature in the form of books, journal articles, and the internet, which after being collected are analyzed descriptively. The results of the study are muzara’ah is cultivating other people's land such as rice fields or fields in exchange for a portion of the yield (one-half, one-third, or one-quarter), while the labor costs and seeds are borne by the landowner. Ulama have different opinions about the law of muzara’ah, some are permissible and some are forbidden. For those who allow, muzara’ah must meet the pillars and conditions that have been determined. Rukun muzara'ah is landowners, farmers/cultivators, objects of muzara'ah, and Ijab and qabul. The practice of muzara'ah refers to the principles of the Profit and Loss Sharing System. In optimizing the muzara'ah contract on Islamic banks, it is necessary to improve the bank system according to the real vision of the Islamic bank and improve the agricultural system. Muzara'ah financing is very important for farmers who want to develop their agricultural land so that they can create mutual benefit, which means good quality and income from individuals and socially. Therefore, Islamic banks play an important role in implementing the muzara'ah contract in Indonesia, of course with the support of the community and government, including through controlling demand and supply, fixing prices, spurring the emergence of an investment climate, not stopping improving the quality of human resources, and maximizing technology.